Mechanical behavior of single concrete frame strengthened with externally prestressed cables - Xudong Gao; Jiying Shang; Yu Song (PLoS ONE, 2026)
Due to the long-term service of building structure in life, the functional degradation of components leads to the reduction of the bearing capacity of the structure, which, however, results in potential safety hazards. External prestressing reinforcement technology can make the existing structure more capable of supporting potential future loads and seismic actions by applying a reaction force to the structure. For the frame structure, the current research results mainly focuses on the external prestressing reinforcement of the beam, but the research on the full reinforcement on the beam and column of the frame structure is less attentively scrutinized up to now. Therefore, the method of full reinforcement of the beam and the column in frame structure is put forward herein, and the deflection-load curve of single concrete frame under vertical load was studied. The stress variation law of stirrup in the middle of frame beam and the internal force variation law of cable and hoop stirrup were analyzed. The results show that the plastic zone can be transferred from the end of the frame beam to the joint position of frame, and that the maximum plastic strain of the structure decrease by 70.65% with the increasing cable sag. Besides, the bearing capacity and yield load increase with the increase in cable sag and stirrup area, the yield load of the stirrup increased by 64.03%., and the cable prestress decreases with the increase in cable sag and cross-sectional area. Unlike previous studies that mainly focused on externally prestressed strengthening of beam-type members, this study proposes an integrated full reinforcement method for both beams and columns in RC frame structures. The novelty lies in combining beam external prestressing and column external hoop-stirrup confinement within one unified frame system and in clarifying the influences of cable sag, cable area, and hoop-stirrup area on the mechanical behavior of the reinforced frame.